Memecahkan masalah geografi melalui problem based learning - Sujiono Sujiono; Budi Handoyo; I Nyoman Ruja (Jurnal Teori dan Praksis Pembelajaran IPS, 2017)
This study aims to determine the effect of Problem Based Learning model on geography problem-solving sklills. This research model is quasi experiment with non-equivalent control group design. The subjects of the study were the students of XI IPS SMA Negeri 1 Pulau Laut Timur, academic year 2016/2017. The assessment instrument is an essay test based on an indicator of problem solving skills, ie (1) identifying problems; (2) formulate the problem; (3) finding alternative solutions; (4) choose alternative solutions; and (5) make conclusions. Data analysis using independent sample t-test model with 5% significance level. The results showed that there is an influence of PBL model on geography problem-solving sklills. The geography problem-solving skills of experimental class with PBL model is higher than control class with conventional model. Suggestion given, that is to make a plan of learning well and doing learning PBL on outdoor study. KeywordsProblem Based Learning, problem-solving skills, geography http://dx.doi.org/10.17977/um022v2i22017p072